Форми та методи реалізації змісту формування медіакомпетентності майбутніх лікарів в медичному університеті - Мурзіна, Олена Анатоліївна; Murzina, O. A. (My University, 2025)
У статті розкрито форми та методи, за допомогою яких здійснюється реалізація змісту формування медіакомпетентності майбутніх лікарів у процесі доклінічної професійної підготовки в медичному університеті. Пропонуємо комплексне застосування традиційних та інноваційних форм організації освітнього процесу в медичному університеті. До основних методів відносимо нетрадиційні, інтерактивні методи навчання; есе; дослідницький метод; презентації освітньо-наукової діяльності; метод проєктів; портфоліо; індивідуальні завдання на платформі edX; індивідуальні завдання в додатку Office 365 Teams. Впровадження в освітній процес запропонованих форм та методів сприяє ефективному формуванню медіакомпетентностей майбутніх лікарів на етапі доклінічної професійної підготовки в медичному університеті. The article reveals the forms and methods by which the content of the formation of media competence of future doctors is implemented in the process of preclinical professional training at a medical university. The structure and content of the programs of educational disciplines are outlined which allow future doctors to form the components of the doctor’s media competence. This is facilitated by the comprehensive use of traditional and innovative forms of organizing the educational process at a medical university. Innovative forms provide the necessary “innovative climate” in higher medical education institutions. Such forms contribute to the development of creativity and critical thinking of future doctors, lay the foundation for further understanding and improvement of one’s medical knowledge, successful application of acquired knowledge in practice. The introduction of innovative forms of the formation of media competence of future doctors helps to prepare highly qualified and competitive specialists to be able to perform scientific research, professional and creative tasks. Innovative forms make it possible to move from studying an abstract subject to perceiving it as a means of communication and thinking and switch over from educational and cognitive activity to a modern, creative level. The introduction of innovative forms significantly improves the quality of presenting educational material and the effectiveness of its assimilation by students, enriches the content of the educational process, increases motivation for learning, and creates conditions for closer communication between the student and the teacher. Therefore, the use of innovative forms is extremely important in the learning process at the stage of preclinical professional training at a medical university. The main methods include non-traditional, interactive teaching methods; essay; research method; presentations of educational and scientific activities; project method; portfolio; individual tasks on the edX platform; individual tasks in the Office 365 Teams application. The introduction of the proposed forms and methods into the educational process contributes to the effective formation of media competencies of future doctors at the stage of preclinical professional training at a medical university.
Forms and methods of implementing the content of forming media competence of future doctors at a medical university
Keywords: медіакомпетентність; медіакомпетентність лікаря; доклінічна професійна підготовка; форми; методи; media competence; media competence of a doctor; preclinical professional training; forms; methods